The Protection of Labor Rights on the Court System - Musakhonovich, Mamasiddikov Muzaffarkhon; Esirgapovich, Esanov Azamat; Jaelani , Abdul Kadir; Wan Khairuldin , Wan Mohd Khairul Firdaus; Luthviati, Resti Dian (Journal of Human Rights, Culture and Legal System, 2024)
Protection of labor rights is critical to ensuring fairness and justice in the workplace. When employees' rights are violated, they can pursue legal redress through the justice system. However, realizing equitable outcomes is frequently impeded by obstacles in accessibility and enforcement. This research analyzes how the justice system can safeguard and enforce labor rights. This research uses normative legal research that employs comparative, legislative, and conceptual methodologies. The research results show that First, Indonesia has labor laws in place. However, the current regulations continue to encounter numerous challenges, including the lengthy and intricate judicial system mechanism and the discrepancy between theoretical regulations and practical implementation. Consequently, expediting the litigation mechanism and reforming the current regulations to protect labor rights is imperative. Second, Indonesia's labor regulations are deemed to be more responsive to the dynamics of contemporary industrial relations than those of Uzbekistan. Uzbekistan must guarantee the protection of workers' and employers' rights, simplify the litigation process, strengthen the competence of judges, and harmonize and reconstruct labor regulations with civil procedural law. Third, it is recommended that Uzbekistan establish a special industrial relations court, revise the rules on evidence and dispute resolution procedures, and enhance the competence of justices through specialized training. This reconstruction will establish a more equitable, efficient, and pertinent system to the current state of employment.